2017
DOI: 10.1016/j.cellsig.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Differential manipulation of arrestin-3 binding to basal and agonist-activated G protein-coupled receptors

Abstract: Non-visual arrestins interact with hundreds of different G protein-coupled receptors (GPCRs). Here we show that by introducing mutations into elements that directly bind receptors, the specificity of arrestin-3 can be altered. Several mutations in the two parts of the central “crest” of the arrestin molecule, middle-loop and C-loop, enhanced or reduced arrestin-3 interactions with several GPCRs in receptor subtype and functional state-specific manner. For example, the Lys139Ile substitution in the middle-loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 84 publications
(166 reference statements)
0
19
0
Order By: Relevance
“…The HEK293 cells genome-edited to lack expression of both arrestin-2 and arrestin-3 have also been used to complement other approaches. In studies of mutated variants of arrestin-3 that appeared to interact spontaneously with the M2 muscarinic acetylcholine receptor it was concluded that Lys 139 Ilearrestin-3 was indeed able to interact with this receptor in an agonist-independent fashion [48]. In a similar vein, [49] used HEK293 cells lacking both arrestin-2 and arrestin-3, but also engineered additionally to lack expression of the endogenously expressed 2-adrenoceptor, to study functional outcomes of two conformations (tail and core) of GPCR-arrestin complexes.…”
Section: Elimination Of Arrestinsmentioning
confidence: 99%
“…The HEK293 cells genome-edited to lack expression of both arrestin-2 and arrestin-3 have also been used to complement other approaches. In studies of mutated variants of arrestin-3 that appeared to interact spontaneously with the M2 muscarinic acetylcholine receptor it was concluded that Lys 139 Ilearrestin-3 was indeed able to interact with this receptor in an agonist-independent fashion [48]. In a similar vein, [49] used HEK293 cells lacking both arrestin-2 and arrestin-3, but also engineered additionally to lack expression of the endogenously expressed 2-adrenoceptor, to study functional outcomes of two conformations (tail and core) of GPCR-arrestin complexes.…”
Section: Elimination Of Arrestinsmentioning
confidence: 99%
“…38 Mutants were tested for their binding to β2AR, M2 muscarinic receptor, D1 and D2 dopamine receptors, and Y1 and Y2 neuropeptide Y receptors. 5052 The results were encouraging. Replacement of just two residues enhanced arrestin-3 preference for some receptors over others ~50–60-fold.…”
Section: Receptor Specificity: Selective Targeting Of Certain Gpcrs?mentioning
confidence: 93%
“…51 Certain mutations selectively affected arrestin interactions with inactive (predocking) and activated GPCRs. 50,52 The good news is that these data suggest that the construction of nonvisual arrestins with relatively narrow receptor specificity is feasible. The bad news is that testing even a few dozen arrestin mutants with ~400 nonodorant GPCRs expressed in every mammalian species is hardly realistic.…”
Section: Receptor Specificity: Selective Targeting Of Certain Gpcrs?mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the targeted manipulation of these putative receptor-discriminator residues suggest that the construction of nonvisual arrestins with narrow receptor specificity is feasible: certain double mutants demonstrate 50–60-fold preference for some GPCRs over others, 19 and a number of mutations differentially affect arrestin interactions with distinct functional forms of several GPCRs. 101103 Generally speaking, preactivating mutations often reduce receptor specificity of arrestins. 94,96 However, this is so in case of active phosphorylated receptors, whereas the same mutations enhance binding only to cognate unphosphorylated GPCRs.…”
Section: Enhanced Arrestins: Compensation Of Excessive Gpcr Activitymentioning
confidence: 99%